TPO’s Perspective towards Role of Social Media Marketing Platforms in Campus Placement Strategy: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Campus Placements are one of the most crucial services professional institutions offers to their students. It is considered to be a significant factor for both the educational institutions and corporate, also are the necessity of contemporary education model. Campus Placement department’s or TPO’s every year in placement season comes up with many creative strategies to mark themselves in front of industries that ensure and provide ideal placements for their students. A brief study is undertaken to identify understand the TPO’s perspective thought process towards using social media networking platforms in their campus placement strategy.